Influence of orthodontic archwire (nickel–titanium versus copper–nickel–titanium) on pain in adult patients in the aligning phase of treatment with self-ligating brackets (two months of follow-up): a prospective observational pilot study - Raquel Marzal; Alberto Albaladejo; Daniel Curto; Adrián Curto (Head & Face Medicine)
Abstract Background The aim of this pilot study was to analyze the influence of a nickel–titanium archwire (NiTi) and a copper–nickel–titanium archwire (Cu-NiTi) on pain levels in adult patients during the first two months of orthodontic treatment with self-ligating brackets. Methods This prospective observational pilot study was carried out at the Dental Clinic of the University of Salamanca between 2023 and 2024. This study analyzed 30 adult orthodontic patients who began treatment with self-ligating brackets. The participants were distributed into two study groups (n = 15) for treatment with initial NiTi and Cu-NiTi archwires. At the beginning, a 0.014-inch archwire was used, and a 0.016-inch archwire was used after a month. The level of pain was measured using a visual analog scale (VAS) at the beginning of treatment (T0), at one month (T1), and at two months (T2). At each time point (T0, T1, and T2), pain was measured at baseline and at 4, 24, and 48 h after archwire placement or replacement. The data were analyzed using Spearman’s correlation coefficient and the Mann–Whitney test (p < 0.05). Results The mean age of the participants (n = 30) was 31.34 (± 6.05) years. The maximum pain peak was in the first 48 h after placing the initial archwire (5.57 ± 1.72). The age and sex of the participants did not influence the pain levels in the sample studied. The composition of the orthodontic archwire only influenced the pain levels at the beginning of treatment (T0) (p < 0.05); in this case, the NiTi group (1.73 ± 1.53) described a higher level of pain than that of the Cu-NiTi group (1.07 ± 1.36); in the rest of the follow-up period, no significant differences were observed. Conclusions Within the limitations of this study, we observed that the orthodontic archwire material (nickel–titanium versus copper–nickel–titanium) only influenced pain levels at the beginning of orthodontic treatment.